Organic materials in civil engineering - Mouton, Yves (ISTE, 2006)
A complete inventory of organic materials and products for civil engineering-from bitumen for roads and geotextiles for retaining walls to membranes for tunnels and reservoir waterproofing-are provided in this resource. Chapters address various types and characterizations of organic materials such as polymers and adhesives. Also includes information on the regulations of organic materials and their predicted useful life as well as expert predictions for the future